2017
DOI: 10.1080/15592324.2017.1370164
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory interplay betweenLEAFY, APETALA1/CAULIFLOWERandTERMINAL FLOWER1: New insights into an old relationship

Abstract: The gene regulatory network comprised of LEAFY (LFY), APETALA1 (AP1), the AP1 paralog CAULIFLOWER (CAL), and TERMINAL FLOWER1 (TFL1) is a major determinant of the flowering process in Arabidopsis thaliana. TFL1 activity in the shoot apical meristem provides inflorescence identity while the transcription factors LFY and AP1/CAL confer floral identity to emerging floral primordia. It has been thought that LFY and AP1/CAL control the onset of flowering in part by repressing TFL1 expression in flowers. However, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Broadly speaking, TFL1 promotes IM identity, while LFY and AP1 promote FM identity. Therefore, it has been proposed that differences in their expression patterns or function can explain much of the diversity of inflorescence architectures observed among angiosperms (Ratcliffe et al, 1999;Blázquez et al, 2006;Benlloch et al, 2007;Serrano-Mislata et al, 2017). Briefly, TFL1, a PEBP, is specifically expressed in the center of the I 1 and I 2 , and promotes IM identity by repressing LFY and its direct target AP1 (and its paralog CAULIFLOWER, CAL) to prevent early inflorescence termination (Mandel et al, 1992;Weigel et al, 1992;Weigel and Nilsson, 1995;Parcy et al, 1998;Teo et al, 2014).…”
Section: Modifications In Inflorescence Architecture During Plant Domesticationmentioning
confidence: 99%
“…Broadly speaking, TFL1 promotes IM identity, while LFY and AP1 promote FM identity. Therefore, it has been proposed that differences in their expression patterns or function can explain much of the diversity of inflorescence architectures observed among angiosperms (Ratcliffe et al, 1999;Blázquez et al, 2006;Benlloch et al, 2007;Serrano-Mislata et al, 2017). Briefly, TFL1, a PEBP, is specifically expressed in the center of the I 1 and I 2 , and promotes IM identity by repressing LFY and its direct target AP1 (and its paralog CAULIFLOWER, CAL) to prevent early inflorescence termination (Mandel et al, 1992;Weigel et al, 1992;Weigel and Nilsson, 1995;Parcy et al, 1998;Teo et al, 2014).…”
Section: Modifications In Inflorescence Architecture During Plant Domesticationmentioning
confidence: 99%
“…The LFY and AP1/CAL are generally believed to suppress flowering by inhibiting the expression of the TFL1 gene in flowers. However, some studies have indicated that the TFL1 transcription was inhibited by AP1 but promoted by LFY (Shannon and Meeks-Wagner, 1991;Liljegren et al, 1999;Pillitteri et al, 2004;Serrano-Mislata et al, 2017). In the mutant strains without TFL1 function, the inflorescent meristem was rapidly transformed to the floral meristem, which significantly promoted flowering (Banfield and Brady, 2000).…”
Section: Genes That Inhibit Plant Floweringmentioning
confidence: 99%
“…On the contrary, overexpression of TFL1 in Arabidopsis thaliana could inhibit the expression of LFY and AP1, and thus delay flowering and increase inflorescence branching (Cheng et al, 2018). AP1 protein and its homologs CAULIFLOWER (CAL) and FRUITFULL (FUL) in Arabidopsis thaliana could inhibit the expression of TFL1 gene (Parcy et al, 2002), while LFY protein can promote the expression of TFL1 gene (Serrano-Mislata et al, 2017). Arabidopsis ARGONAUTE1 (AGO1) could also inhibit the expression of TFL1 gene and regulate inflorescence development (Fernandez-Nohales et al, 2014).…”
Section: Introductionmentioning
confidence: 99%